Utility of Transcutaneous Bilirubinometer in Tertiary Care Hospital - Kumar, Vijay; Kahlon, Pardeep Singh; Singh, Palwinder; Singh, Kamail; Sharma, Anubha (Journal of Nepal Paediatric Society, 2017)
Introduction: Hyperbilirubinemia is one of the most vexing problems that may occur in 60% of term and 80% of preterm neonates. In order to reduce the risk of developing serious hyperbilirubinemia, it is vital to identify jaundiced infants who are in need of treatment as soon as possible. The objectives of this study were to find whether transcutaneous bilirubin (TcB) measurement correlates with total serum bilirubin (TSB) levels, measured with standard laboratory method and to analyse the effect of gestational age, birth weight and postnatal life on TcB and TSB. Material and Methods: A prospective study was conducted in the Department of Paediatrics, Government Medical College, Amritsar on 300 neonates with visible jaundice. These neonates were divided into various groups depending upon gestational age, birth weight and day of life. TcB readings were recorded at forehead and sternum and serum bilirubin level was measured within 30 minutes. Test of significance applied was unpaired T-test; mean value, p-value, standard deviation and Pearson's correlation coefficient 'r' were calculated. Results: Overall Mean value TcB at forehead was 15.32 with SD ± 2.75, mean TcB at sternum was 14.94 with SD ±2.51, mean value of TSB was 13.80 with SD ±2.15. Pearson’s correlation coefficient r was 0.895 for TcB forehead vs TSB, 0.903 for TcB sternum vs TSB and 0.966 between TcB forehead vs TcB sternum. Conclusion: TcB levels correlates well with the gold standard measurement of TSB. Gestational age, birth weight and day of life had no effect on TcB and TSB correlation. Transcutaneous bilirubinometer can thus be used to measure bilirubin level as a screening method for neonatal hyperbilirubinemia.